Assessing the Spillover Effects of FDI to the Philippines - Rafaelita M. Aldaba; Fernando T. Aldaba (Philippine Institute for Development Studies (PIDS), 2010)
The experience of the Philippines shows that FDI spillover effects are not automatically generated. Opening up the economy to FDI has contributed to the country's exports of high-technology products and overall economic growth. However, the spillover effects of FDI to domestic firms have remained limited due to the domestic firms' weak competitiveness and inability to absorb the technology or knowledge being transferred. The government needs to adopt a more comprehensive approach that would combine industrial policy to improve and develop domestic parts and supplier firms with measures to create an environment conducive to the creation and expansion of FDI-related spillovers as well as increase participation in higher segments of industry value chain.
Keywords: 330; Philippines; regional production networks (RPNs); Philippine foreign direct investment; FDI spillover effects; horizontal; forward; and backward linkages; Auslandsinvestition; Spillover-Effekt; Wirtschaftswachstum; Industriepolitik; Internationaler Wettbewerb; Philippinen